IMPORTANCE OF BIFID MANDIBULAR CANAL IN IMPLANTOLOGY AND IN ORAL SURGERY: REVIEW OF THE LITERATURE AND REPORT OF THREE CASES - Nihat Akbulut; Sibel Akbulut; Bengi Oztas; Sebnem Kursun; Emrah Soylu; Orhan Guven (Cumhuriyet University, 2017)
The mandibular canal or the inferior alveolar canal typically extends from the mandibular foramen to the mental foramen and includes the inferior alveolar artery, vein and the inferior alveolar nerve. During embryonic development three canals fuse to form a single canal. Failure of these canals to fuse can explain presence of multiple canals in some individuals. It is important to localize the course of the mandibular canal at the site of implant placement as altered sensation of the inferior lip due to inferior alveolar nerve injury. It is one of the most serious complication of mandibular implant surgery. Also the difficulty in performing mandibular anesthesia is the other problematic issue for patients and the clinicians. The purpose of this study is to call attention to a rare anatomical variation. This case report reveals an unusual variant of the bifid mandibular canals. Three new cases, two of which are in the same family, have been presented.